DIGITAL MEDIA INTEGRATION STRATEGIES IN ENGLISH INSTRUCTION BASED ON THE SAMR FRAMEWORK - Febri Utomo, Widodo; Akhsanudin Khanafi; Faiq Ridlo Al Amin (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This research examines the use of the Substitution, Augmentation, Modification, Redefinition (SAMR) framework as a foundation for strategies integrating digital media into English instruction at Madrasah Ibtidaiyah. The study is grounded in the need to enhance instructional quality at the Islamic elementary level through technologies aligned with learning objectives, learner characteristics, and infrastructural constraints. Through a synthesis of theoretical and empirical literature on technology-enhanced learning, multimedia design, formative assessment, and English for Young Learners, the focus is directed toward mapping strategies at each SAMR level along with illustrative applications, learning outcome indicators, enabling and limiting factors, and practical implications for teachers. Findings indicate that Substitution and Augmentation improve efficiency, clarity of instruction, and feedback, whereas Modification and Redefinition transform task design through collaboration, multimodality, and authentic audiences. Integrating SAMR with TPACK, multimedia principles, and formative assessment yields a staged development pathway ranging from limited-device contexts to creative, product-oriented projects. The study recommends context-responsive strategies to ensure that technology integration produces measurable impacts on language attainment, motivation, and student engagement.